Relationships between District Size, Socioeconomics, Expenditures, and Student Achievement in Washington - Vince Diaz (The Rural Educator, 2008)
The purpose of this article is to describe the relationship between district size, socioeconomic status, actual levy percentages, and their predictive influence on the 2003 Washington Assessment of Student Learning results for 4th and 7th grade students in Reading and Mathematics. The convenient sample was 82 Washington State 2nd-Class school districts with enrollments between 500-2,000 students. The results indicated: (a) no significant correlations between achievement and district size; (b) socioeconomic status was the best predictor of achievement; and (c) actual levy percentages and student outcomes were significantly correlated in the positive direction.